A review of the technical and economic evaluation techniques for shale gas development. (15th June 2015) - Yuan, Jiehui; Luo, Dongkun; Feng, Lianyong
Graphical abstract: Highlights: We review the technical–economic evaluation techniques for shale gas development. The current status of the technical–economic evaluation techniques is investigated. Recent evolution and development of the evaluation techniques are identified. Future probable focuses and trends of the evaluation techniques are presented. Abstract: Shale gas, due to its clean-burning and efficient nature, is becoming an increasingly promising alternative energy resource. It is commonly held that promoting shale gas development will gradually play a significant role in meeting the energy needs of economic and social development as well as reducing harm to the environment. Given the significant implications, many countries are pursuing shale gas opportunities. However, numerous concerns have been raised about the economics of shale gas development, as it is difficult to evaluate. Accurately evaluating the economic viability of shale gas development to reduce investment risks and increase investment opportunity is the key issue that needs to be urgently addressed. This paper presents a systematic review and examination of the technical and economic evaluation techniques for the development of shale gas to provide an overview of their current status. Over time, some progress has been made in existing technical–economic evaluation techniques. It is worth noting that these techniques need to be further improved to more precisely assess the economic feasibility of developing shale gas for assisting investment decisions effectively. For this reason, various potentially useful ideas and approaches are presented to propose some potential improvement in evaluation techniques for shale gas development, which may materialize in possible future trends.